MICHAEL PIGGOTT, Archives and Societal Provenance: Australian Essays - Eastwood, Terry (Archivaria, 2015)
Archives and Societal Provenance: Australian Essays. MICHAEL PIGGOTT. Oxford: Chandos Publishing, 2012. xxiv, 334 pp. ISBN 978-1- 84334-712-5 (print), ISBN 987-1-78063-378-7 (e-book)